Expressing Enhanced Inhibitory Effects toward Arachidonic Acid Induced Platelet Activation: Design, Synthesis, DFT Calculations and in vitro Evaluation of Imatinib Analogues. Issue 11 (22nd March 2023) - Kosma, Anna; Pantazi, Despoina; Voulgari, Pinelopi; Ntemou, Nikoleta; Brentas, Alexios; Alivertis, Dimitrios; Siskos, Michael G.; Tselepis, Alexandros D.; Skobridis, Konstantinos
Abstract: Encouraged by the excellent antiplatelet properties of novel imatinib and nilotinib analogues in our previous study and based on a fact that slight structural changes, such as the incorporation of different substituents at the final phenyl ring of imatinib and nilotinib, have a strong impact on their antiplatelet potency, two pairs of constitutional isomers of the imatinib analogues 1, 2 and 3, 4, have been designed, synthesized and evaluated for their antiplatelet characteristics. The structure geometry of the imatinib analogues 1 –4 and NBO (Natural Bond Orbital) charges of the lower energy conformation each of the analogues were explored by DFT. Molecular docking studies were also performed. All compounds were less efficient in inhibiting platelet aggregation induced by ADP or TRAP‐6 in comparison with arachidonic acid (AA). Similar results were obtained for the membrane expression of P‐selectin. The most active compound was also tested to inhibit c‐Src kinase. The present study demonstrates that appropriate modifications of the imatinib structure, may confer on this molecule potent antiplatelet characteristics. Abstract : Two pairs of constitutional isomers, analogues of imatinib, have been designed, synthesized and evaluated for their antiplatelet characteristics. The structure geometry of the imatinib analogues and NBO charges of the lower energy conformation each of the analogues were explored by DFT. The present study demonstrates that appropriate modifications of the imatinib structure, may confer on this molecule potent antiplatelet characteristics.